2017
DOI: 10.1002/anie.201704682
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Catalyzed C−H Functionalizations: Hydroarylations and Alkenylations Involving an Unexpected Heteroaryl Shift

Abstract: A manganese-catalyzed regio- and stereoselective hydroarylation of allenes is reported. The C-H functionalization method provides access to various alkenylated indoles in excellent yields. Moreover, a hydroarylation/cyclization cascade involving an unexpected C-N bond cleavage and aryl shift has been developed, which provides a new synthetic approach to substituted pyrroloindolones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(42 citation statements)
references
References 80 publications
0
42
0
Order By: Relevance
“…[5] Following the concept of HA, pyrroles can be synthetized from unsaturated 1,4-diols and primary amines. [7] Moreover, Beller and co-workersh ave reported at hree-component synthesis of pyrroles by using a[ Ru 3 (CO) 12 ]/Xantphos catalytic system.T he authors proposed that the reaction might proceed through the AD concept. [7] Moreover, Beller and co-workersh ave reported at hree-component synthesis of pyrroles by using a[ Ru 3 (CO) 12 ]/Xantphos catalytic system.T he authors proposed that the reaction might proceed through the AD concept.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Following the concept of HA, pyrroles can be synthetized from unsaturated 1,4-diols and primary amines. [7] Moreover, Beller and co-workersh ave reported at hree-component synthesis of pyrroles by using a[ Ru 3 (CO) 12 ]/Xantphos catalytic system.T he authors proposed that the reaction might proceed through the AD concept. [7] Moreover, Beller and co-workersh ave reported at hree-component synthesis of pyrroles by using a[ Ru 3 (CO) 12 ]/Xantphos catalytic system.T he authors proposed that the reaction might proceed through the AD concept.…”
mentioning
confidence: 99%
“…[8] The replacemento fn oble metal catalystsb yf irst-row transition metal catalysts is highly desirable owing to ecological and economic benefits andm ay also lead to the discovery of new chemicalr eactivity. [10][11][12] In our continuouse fforts to develop new sustainablet ransformations enabledb ym etal-ligand catalysts, [13,14] we now report an unprecedented manganese-catalyzed constructiono fp yrroles startingf rom readily availables ubstrates:1 ,2-diols, ketones, and primary amines (Scheme 1C). [10][11][12] In our continuouse fforts to develop new sustainablet ransformations enabledb ym etal-ligand catalysts, [13,14] we now report an unprecedented manganese-catalyzed constructiono fp yrroles startingf rom readily availables ubstrates:1 ,2-diols, ketones, and primary amines (Scheme 1C).…”
mentioning
confidence: 99%
“…Further, redox‐neutral C−H bond alkenylation of indoles was studied by hydroarylation of allenes to access diversely substituted C‐2 olefinated indoles. Mechanistic studies suggested that the initially formed cyclometalated manganese reacts with an allene via a manganacycle to provide the alkenylated product . The manganese catalyzed C−H activation in continuous flow was reported by Ackermann and co‐workers, which enables the efficient hydroarylation within 20 minutes .…”
Section: Alkenylation Reactionsmentioning
confidence: 97%
“…[2] While the ligating ability of the DG is ap rerequisite,t he employment of permanent, poorly functionalizable DGs has restricted their applications.P yridines and pyrimidines represent typical "permanent" directing groups in numerous C À Ha ctivation systems (Scheme 1a). [4] To overcome the limitation of permanent DGs,m ultifunctionality as nucleophiles,e lectrophiles,o xidants, [5] and 1,3-dipoles [6] has been imparted to the DGs in post-coupling transformations.D espite this progress,o ther kind of multifunctionality for DGs remains in great demand. [3] Very recently,t hese DGs have been shown to undergo post-coupling migration in af ew reports.…”
mentioning
confidence: 99%
“…Thus,the pyridine directing group acts as aC 4s ynthon in this dehydocyanative coupling.S olvent studies returned MTBE as the optimal medium (entries [1][2][3][4][5]. Ar eaction occurred with MnBr(CO) 5 as the catalyst in the presence of NaOAc, affording the desired transannulation product 3aa in low yield (entry 1).…”
mentioning
confidence: 99%